Question 7.SP.36: Solve the following impact equations for unknowns v1 and v2:......

Solve the following impact equations for unknowns v_{1} and v_{2} :

\begin{array}{c}e=\frac{v_{2}-v_{1}}{u_{1}-u_{2}}\qquad \qquad &(1) \\  \\m_{1} u_{1}+m_{2} u_{2}=m_{1} v_{1}+m_{2} v_{2}\qquad \qquad &(2)\end{array}

where e= coefficient of restitution

u_{1}, u_{2}= speed of bodies 1 and 2 , respectively, before impact

v_{1}, v_{2}= speeds of bodies 1 and 2, respectively, after impact

m_{1}, m_{2}= masses of bodies 1 and 2 , respectively

Step-by-Step
The 'Blue Check Mark' means that this solution was answered by an expert.
Learn more on how do we answer questions.

Multiply (1) by \left(u_{1}-u_{2}\right) m_{1} to obtain

e m_{1}\left(u_{1}-u_{2}\right)=m_{1} v_{2}-m_{1} v_{1}\qquad \qquad (3)

Add (2) and (3) to get

m_{1} u_{1}+m_{2} u_{2}+e m_{1}\left(u_{1}-u_{2}\right)=\left(m_{2}+m_{1}\right) v_{2}\qquad \qquad (4)

Then,

v_{2}=\frac{m_{1} u_{1}(1  +  e)  +  u_{2}\left(m_{2}-e m_{1}\right)}{m_{2}  +  m_{1}}

Similarly, \qquad \qquad \qquad v_{1}=\frac{m_{2} u_{2}(1  +  e)  +  u_{1}\left(m_{1}-e m_{2}\right)}{m_{2}  +  m_{1}}

Related Answered Questions

Question: 7.SP.38

Verified Answer:

This is the case when one body absorbs the other o...
Question: 7.SP.37

Verified Answer:

For elastic impact, substitute e=1 [/latex...
Question: 7.SP.31

Verified Answer:

ANALYSIS Initially the projectile is at rest in th...